Hot-injection strategy for 1-min synthesis of carbon dots from oxygen-containing organic solvents: Toward fluorescence sensing of hemoglobin. (June 2019) - Hu, Yaoping; Gao, Zhijin
Abstract: Here, we present a rapid and general fabrication methodology for fluorescent carbon dots (CDs) via injecting various oxygen-containing organic solvents including acetone, ethanol, ethyl acetate, tetrahydrofuran, and diethyl ether into hot concentrated sulfuric acid. All these small organic molecules are recognized as common, cheap, and abundant carbon precursors, which can convert into CDs just in 1 min through protonation, polymerization and aromatization. The as-prepared CDs with disordered amorphous cores and plentiful oxygenous groups show fascinating photoluminescence features, that can be used for sensitive and selective detection of hemoglobin (Hb) based on fluorescence quenching. The linear detection range is estimated to be 2–360 nM and the limit of detection is as low as 0.79 nM. After careful investigations, the inner filter effect is proposed to explain the sensing mechanism because the absorption band of Hb fully covers the emission spectrum of CDs and the fluorescence lifetime of CDs remains nearly constant after addition of Hb. The sensor is successfully applied for Hb detection in human blood samples, exhibiting a great potential for quantitative analysis of Hb in complex biological matrices. Graphical abstract: One-minute synthesis of carbon dots from oxygen-containing organic solvents using a hot-injection strategy, and the application of CDs for fluorescence detection of hemoglobin. Image 1 Highlights: Using the hot-injection strategy, various oxygen-containing organic solvents can convert into carbon dots just in 1 min. The carbon dots can be used for sensitive and selective detection of hemoglobin based on fluorescence quenching. The inner filter effect is proposed to explain the sensing mechanism.